2015
DOI: 10.1111/jnc.13399
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillar acidic protein in the cerebrospinal fluid of Alzheimer's disease, dementia with Lewy bodies, and frontotemporal lobar degeneration

Abstract: Biomarkers in the cerebrospinal fluid (CSF) are currently regarded as indispensable indicators for accurate differential diagnosis of neurodegenerative disorders. Although high levels of astrocyte-secreted glial fibrillar acidic protein (GFAP) in the CSF of patients with Alzheimer's disease (AD) have been reported, the levels of GFAP in the CSF have not been fully investigated in other neurological disorders that cause dementia, such as dementia with Lewy bodies (DLB) and frontotemporal lobar degeneration (FTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 10 publications
14
97
0
2
Order By: Relevance
“…Our results support previous observations of increased YKL-4023 24 and GFAP28 in CSF of patients with sFTD and we could demonstrate similar changes in gFTD. Thus, our data indicate a similar neuroinflammatory profile in gFTD and sFTD and support the notion that it is a shared mechanism in gFTD and sFTD pathophysiology.…”
Section: Discussionsupporting
confidence: 93%
“…Our results support previous observations of increased YKL-4023 24 and GFAP28 in CSF of patients with sFTD and we could demonstrate similar changes in gFTD. Thus, our data indicate a similar neuroinflammatory profile in gFTD and sFTD and support the notion that it is a shared mechanism in gFTD and sFTD pathophysiology.…”
Section: Discussionsupporting
confidence: 93%
“…Glial fibrillary acidic protein (GFAP) is also known as a marker of astrocytosis in neurodegeneration associated with neurological disorders. Higher levels of GFAP in CSF have been reported in neurodegenerative disorders including AD, dementia with Lewy bodies (DLB), and frontotemporal dementia (FTLD) [18]. GFAP levels in CSF are also elevated in Creutzfeldt-Jakob disease (sCJD) patients [29].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the current literature, this is the largest quantitative CSF proteome for Alzheimer’s disease reported thus far. Among the proteins that were differentially expressed in patients with AD were neuronal cell adhesion molecule-1 [16, 17], glial fibrillary acidic protein [18], microtubule associated protein Tau [18], neuronal pentraxin 2 [19], VGF nerve growth factor inducible (VGF)[20] and secretogranin II (SCG2)[20], which have already been reported by other groups to be altered in the CSF of AD dementia patients thereby validating the feasibility of our approach. Multiplexed parallel reaction monitoring (PRM) assays developed to quantitate a subset of these candidate biomarkers in CSF confirmed the alterations that were observed in the discovery experiments.…”
Section: Introductionmentioning
confidence: 99%
“…CSF concentration of GFAP has been shown to be elevated in AD, as well as in other neurodegenerative dementias 38 though other studies found no difference between AD and controls or between AD and other neurodegenerative conditions 39 . GFAP has not been demonstrated to be increased in delirium 40 .…”
Section: Neuronal Injury/death Biomarkers In Ad and Deliriummentioning
confidence: 96%